Pengaruh Kompensasi, Motivasi, dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan Pada PT. Pacific Angkasa Abadi - Firdhausiah, Fitri; Baskoro, Heru (SAFE-Network, 2025)
This study aims to analyze the effect of compensation, motivation, and physical work environment on employee performance at PT. Pacific Angkasa Abadi, a manufacturing company engaged in the iron pipe and pipe fitting industry. The background of this study is based on the problem of declining employee performance as seen from work output that does not meet the set targets. The method used in this study is quantitative analysis with data collection through questionnaires distributed to employees. The number of samples used in this study was 56 respondents with a saturated sampling technique. The data obtained were then analyzed using multiple linear regression analysis and partial hypothesis testing using SPSS 25 to determine the effect of each variable on employee performance. The results of the study showed that there was a positive and significant effect between compensation and employee performance, which is in line with previous studies showing that compensation contributes to increased performance. Motivation has a positive and significant effect on employee performance, in addition, the physical work environment has a positive and significant effect on employee performance. All variables play an important role in improving employee performance, which is a key factor in achieving company goals. The conclusion of this study confirms that companies need to pay attention to aspects of compensation, motivation, and the physical work environment to improve overall employee performance.